Modelling of Shear-critical, Lightly Reinforced Concrete T-beams with Externally Bonded CFRP using ATENA Science - Fillbert Hanselly Njoko; Asdam Tambusay; Andrew Jamieson; Benny Suryanto; Priyo Suprobo (Institute of Research and Community Outreach - Petra Christian University, 2023)
This paper presents the finite element modelling of shear-critical reinforced concrete beams strengthened with U-wrapped CFRP fabrics using ATENA. Fracture-plastic constitutive models, implemented in the context of smeared crack and crush-band approach, were employed to represent the nonlinear behaviours of concrete. CFRP U-wraps were modelled as smeared reinforcement and bonded to the concrete surface using an interface element, considering appropriate bond properties. To this end, two large lightly reinforced concrete T-beams from tests undertaken by Brindley in 2018 were analysed and predictions of the load-deflection response and failure mode are presented to demonstrate the accuracy of the modelling. Moreover, parametric analyses were performed to assess the effectiveness of CFRP U-wraps for strengthening deteriorated members. It is shown that the response of the beams can be predicted accurately, capturing successfully the brittle shear failure mode observed experimentally. It is also shown that CFRP U-wraps are useful for reducing the brittleness of shear-critical beams.